Pengaruh Modal Sosial Terhadap Tingkat Pendapatan Pedagang Buah di Pasar Pagi Arengka Kota Pekanbaru - Sahbani, Vina; Nurhamlin, Nurhamlin (Jurnal Ilmiah Wahana Pendidikan, 2025)
This research was conducted at the Pagi Arengka Market in Marpoyan Damai Subdistrict, Pekanbaru City, with the objectives: 1) to understand the forms of capital among fruit vendors at the Pagi Arengka Market in Pekanbaru City, 2) to understand the income levels of fruit vendors at the Pagi Arengka Market in Pekanbaru City, and 3) to understand the relationship between social capital and income levels of fruit vendors at the Pagi Arengka Market in Pekanbaru City. This research employed a quantitative descriptive study using a census sampling technique with 30 fruit vendor respondents. The data collection techniques used were structured interviews, questionnaires, observation, and documentation. The results showed that the social capital forms in this study were strong, with high network numbers at 60.00%, trust at 73.30%, and norms at 60.00%. The income levels in this study were strong, with high income levels at 50.00%, with monthly earnings ranging from IDR 6,001,000 to IDR 9,000,000. The relationship between social capital and income levels was very strong, with a correlation coefficient of 0.9039 and a significance level of 0.000, which is less than 0.05 so that sig < a = hypothesis is rejected, and the alternative hypothesis is accepted. This means that social capital significantly affects the income level of traders with a very strong outcome. The results of this study also showed that the influence of social capital on the income levels of fruit vendors at the Pagi Arengka Market in Pekanbaru City was 90.2%, indicating that social capital plays a dominant role in improving the economic well-being of fruit vendors